Extractive recovery and valorisation of arsenic from contaminated soil through phytoremediation using Pteris cretica. (October 2018) - Eze, Valentine C.; Harvey, Adam P.
Abstract: Contamination of ground water and soil by arsenic poses serious environmental challenges globally. A possible solution to this problem is through phytoremediation using hyper-accumulating plants. This study investigates phytoremediation of soil containing 200 ± 3 mg kg −1 of arsenic using Pteris cretica ferns, and the strategies for arsenic extraction from the ferns biomass and subsequent conversions to valuable arsenic products. The Pteris cretica ferns achieved maximum arsenic accumulations of 4427 ± 79 to 4875 ± 96 mg of arsenic per kg dry biomass after 30 days. Extraction efficiencies of arsenic in the ferns fronds were 94.3 ± 2.1% for ethanol-water (1:1 v/v), 81.5 ± 3.2% for 1:1 (v/v) methanol-water, and 70.8 ± 2.9% for water alone. Molybdic acid process was used to recover 90.8 ± 5.3% of the arsenic, and 95.1 ± 4.6% of the phosphorus in the biomass extract. Quantitative precipitation of Mg3 (AsO4 )2 and Mg3 (PO4 )2 occurred on treatment of the aqueous solutions of arsenic and phosphorus after stripping at pH of 8–10. The efficiencies of Mg3 (AsO4 )2 and Mg3 (PO4 )2 precipitation were 96 ± 7.2% and 94 ± 3.4%, respectively. Arsenic nanoparticles produced from the recovered Mg3 (AsO4 )2, using two-stage reduction process, had average particle diameters of 45.5 ± 11.3 nm. These nanoparticles are potentially valuable for medical applications, while the Mg3 (AsO4 )2 could be converted to more valuable forms of arsenic or used as a pesticide, and the Mg3 (PO4 )2 in fertiliser. Recovery of these valuable products from phytoremediation biomass would incentivise and drive commercial industries' participation in remediation of contaminated lands. Highlights: Phytoremediation of 200 ± 3 mg kg −1 arsenic-contaminated soil using Pteris cretica. Arsenic accumulations between 4427 and 4875 mg kg −1 were achieved after 30 days. Molybdic acid process extracted 90.8 ± 5.3% arsenic and 95.1 ± 4.6% phosphorus. Arsenic and phosphorus recovered as Mg3 (AsO4 )2 and Mg3 (PO4 )2 at >94% efficiencies. Arsenic nanoparticles of 45.5 ± 11.3 nm diameters produced from the Mg3 (AsO4 )2 .